Fischli & Weiss : Flowers & Questions : A Retrospective - Tate Modern, London (London : Tate Modern London, 2006)
Peter Fischli and David Weiss have been collaborating since 1979 on a body of work that humorously celebrates the sheer banality of everyday existence. Utilising a variety of media including photography, film, video, artists' books, installation and sculpture, their work playfully ignores the traditional distinction between high and low art, while at the same time commenting on the human condition. This unique book, developed in collaboration with the artists, accompanies the major touring exhibition and is the most extensive visual record of their extraordinarily varied work yet published. The writers featured include critics, curators, cultural commentators, artists and filmmakers, bringing a variety of voices to hear on a career that defies boundaries as easily as it evades simple classification.
biog. auteurs p. 352-353
biog., ind. tent., gr. tent. p. 346-349, bibliog. p. 350-351
Engels
Catalogue on the occasion of the exhibition "Peter Fischli & David Weiss / Flowers & Questions, a retrospective" at Tate Modern in London, 11.10.2006 - 14.01.2007, at Kunsthaus in Zürich, 08.06.2007 - 09.09.2007, at Deichtorhallen in Hamburg, 16.11.2007 - 03.02.2008
boek
Keywords: Fischli & Weiss